Linguistic and Media Studies Perspectives on Research into Social and Political Polarisation (Vandenhoeck & Ruprecht, 2026)
The causes of polarization existing in Polish society are multifaceted, and cannot be easily elucidated using ordinary demographic variables alone. The collaborative research initiative of linguists and media scholars is therefore not accidental: language is the primary vehicle of communication, and communication constitutes the modus operandi of social existence. Without language, which functions as a cohesive force (a “glue”) of society, any society would be unable to organize itself or sustain in its complexity. In this volume, language serves as both the object of study and the tool utilized for research purposes. The analysis of language utilized by various social actors provides insight into the social processes unfolding within a society.